Construction time, cost and testing data of a prefabricated isolation medical unit for COVID-19 (2020)
Coronavirus Disease 2019 (COVID-19) has been identified as a global pandemic by the World Health Organization (WHO). The breakout of COVID-19 in various countries and regions brings a great threat to people’s life and adds an unprecedented high pressure on healthcare systems. Due to the high infectivity of COVID-19, high standard negative pressure isolation units are required to accommodate the patients with COVID-19 and protect health workers. A novel prefabricated negative pressure isolation medical unit was designed and constructed in Shenzhen, China to help to accommodate the patients with COVID-19. This article provides detailed construction cost, time and testing data for this isolation medical unit. Considering the construction happened during the lockdown in Shenzhen (and in China), the construction cost and time can provide precious and rare information as well as guidelines to construct or expand appropriate medical facilities to accommodate the patients with COVID-19.